To solve this system of equations algebraically, we can set the two expressions for y equal to each other and solve for x:
x^2 −19x + 58 = −3x − 5
Rearranging the terms:
x^2 − 16x + 63 = 0
Now we need to factor this quadratic equation:
(x − 7)(x − 9) = 0
Setting each factor equal to zero:
x - 7 = 0 or x - 9 = 0
x = 7 or x = 9
Now that we have found the values of x, we can substitute them back into one of the original equations to find the corresponding values of y. Let's use y = x^2 − 19x + 58:
For x = 7:
y = 7^2 − 19(7) + 58
y = 49 - 133 + 58
y = -26 + 58
y = 32
So when x = 7, y = 32.
For x = 9:
y = 9^2 − 19(9) + 58
y = 81 - 171 + 58
y = -90 + 58
y = -32
So when x = 9, y = -32.
Therefore, the solution to the system of equations is x = 7, y = 32 and x = 9, y = -32.
Solve the following system of equations algebraically: y= x^2 −19x+58 y, y= −3x−5
1 answer